2011
DOI: 10.1021/cg101489t
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Structures of Cyclic Triimidazole and Its Boric Acid Adduct

Abstract: Cyclic triimidazole, C9H6N6 (1), was prepared by thermolysis of the easily prepared copper imidazolate framework solid, Cu(C3H3N2)2 (2), providing a convenient route to this potentially useful tecton for molecular design. Anhydrous 1 and a hydrate, 1·0.5H2O, were characterized by single-crystal X-ray diffraction. Hydrate 1·0.5H2O contains two crystallographically independent 1 molecules. Supramolecular structures of 1 and 1·0.5H2O feature stacking arrangements in which the 1 molecule deviates from idealized ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…The formula units comprise octahedral hexa‐aqua metal cations [M(H 2 O) 6 ] 2+ capped by the two symmetry‐related tetrahedral anions held in perching tripod positions via three OH(water)⋅⋅⋅Cl(F) hydrogen bonds, and two TT ligands attached to the metal cations via OH⋅⋅⋅N hydrogen bonds (Figure and Table S2 in SI). The Cd‐O distances are equal to 2.287(2) and 2.2857(19) Å in 2 , 3 , and Zn‐O distance is equal to 2.0973(17) Å in 4 , respectively in agreement with literature data …”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The formula units comprise octahedral hexa‐aqua metal cations [M(H 2 O) 6 ] 2+ capped by the two symmetry‐related tetrahedral anions held in perching tripod positions via three OH(water)⋅⋅⋅Cl(F) hydrogen bonds, and two TT ligands attached to the metal cations via OH⋅⋅⋅N hydrogen bonds (Figure and Table S2 in SI). The Cd‐O distances are equal to 2.287(2) and 2.2857(19) Å in 2 , 3 , and Zn‐O distance is equal to 2.0973(17) Å in 4 , respectively in agreement with literature data …”
Section: Resultssupporting
confidence: 90%
“…On the other side, its crystals show a strong, broad, featureless emission centered at 400 nm ( Φ =30 %, λ exc =350 nm) which is the result of the superimposition of a prompt (λ em =400 nm, τ in the nanosecond regime) and a longer wavelength (λ em =525 nm) RTUP which lasts for about 3.6 s (τ av =970 ms) and is affected by the degree of crystallinity but is inert to oxygen. Single crystal XRD analysis revealed that the molecules are slightly twisted with respect to an idealized C 3 h symmetry and stack in face‐to‐face antiparallel packed zigzag columns with distances between centroids of the central rings equal to 3.73 and 3.95 Å (Figure , left) . Such short distances are indicative of strong π–π interactions in the ground state, associated with a large interchromophoric π‐stacking area and formation of H‐aggregates which are responsible for the CIE behavior and are at the basis of the RTUP …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations